ANALYSIS OF THE VOLTAGE-REACTIVE POWER CONTROL MODE IMPACT ON PHOTOVOLTAIC SYSTEMS ENERGY GENERATION CURTAILMENT - WISAM ALI MOHAMAD ISSA (2023)
This work has as its main theme the study of the reduction of grid-connected photovoltaic systems energy production employing voltage-reactive power control due to the prioritization of the reactive power output requested by the algorithm. More specifically, the intended main objective was to study the sensitivity of this curtailment phenomenon relative to the power system line parameters (resistances and inductances), the sazonal variances of the loads demand curves and solar irradiance timeseries, the influence of the electric power system (EPS) voltage regulation devices such as capacitor banks and transformers with tap changers, as well as the intensification of the participation of photovoltaic systems within the EPS. In order to attain the proposed objective, several simulations were executed in three different feeders available in the literature. Based on the results, it was possible to constate, among other conclusions, that when the penetration level of solar distributed generators is low, the efforts of their inverters are more strongly related to the mitigation of voltage regulation issues resulting from the grid own conditions, rather than their own generation. The sazonal characteristic of the loads demand curves, as well as the solar irradiation allowed to observe important differences in the season of the year in which the worst curtailment occured, which also depend on the penetration level of the photovoltaic systems within the grid. It was also verified that even strong grids can present high relative curtailments if they are heavily loaded and the penetration level of the photovoltaic systems within them is low. The influence of the penetration level itself is an important factor, specially if the feeder is weak, a case for which it was verified that the overall curtailment depends more strongly on this variable. Finally, although tap changers demonstrated to predominantly impact positively the required effort from the distributed generation units for voltage support, since they only affect a part of the system, other units located outside of this region may have to sacrifice more their own generation in order to comply with the volt-var, due to the lack of contribution from the inverters located on the mentioned affected section.